SYNTHESIS AND ANTI-BACTERIAL SCREENING OF SOME NOVEL FUSED IMINO PYRIMIDO BENZOTHIAZOLE AND ITS SCHIFF’S BASES - MAYURA KALE; DEEPAK MENE (International Journal of Pharma and Bio Sciences, 2013)
Benzotiazole and pyrimidine have been reported to act as effective pharmacophores. However, much less work as been carried out on these heterocycles fused with each other. In the present study, we report the synthesis of a series of 8-chloro-3-(phenylcarbonoimidoyl)-10a-H-pyrimido [2,1-b][1,3]benzothiazole-2-thiol. This series was synthesized by the reaction of 8-chloro-2-sulfanyl-10a-H-pyrimido [2,1-b][1,3]benzothiazole-3-carbaldehyde with various aromatic amines in presence of dimethyl formamide and sodium sulphide. 2, 8-dichloro-10a-H-pyrimido[2, 1-b][1,3]benzothiazole-3-carbaldehyde was prepared by reaction of N-(6-chloro-1, 3-benzothiazole-2-yl)acetamide with Vilsmeier-Haack reagent. All the synthesized compounds were screened for their anti-inflammatory and anti-bacterial activities. The results of both the studies confirmed the biological potential of these fused heterocycles which can be further used as therapeutic lead for generating new drug candidates.